Formation of cobalt silicide nanoparticles on graphene with a synergistic effect and high stability for ethanol oxidation. Issue 36 (23rd March 2016) - Zhang, Mingmei; Pan, Denghui; Li, Yuan; Yan, Zaoxue; Meng, Suci; Xie, Jimin
Abstract : Stable cobalt silicide (CoSi) with an average diameter of less than 4 nm is uniformly decorated with graphene by a chemical vapor deposition method. Abstract : Stable cobalt silicide (CoSi) with an average diameter of less than 4 nm is uniformly decorated with graphene by a chemical vapor deposition method. Palladium (Pd) is then supported on the CoSi–G composite (Pd/CoSi–G) using an intermittent microwave heating reduction method and this composite is used as an electrocatalyst for ethanol oxidation in alkaline media. The Pd/CoSi–G catalyst exhibits 1.8 and 4.3 times the peak current density compared with Pd loaded on graphene and Vulcan XC-72 carbon, respectively. The significant increase in catalytic activity can be contributed to CoSi benefitting the formation of smaller and highly dispersed Pd particles and the synergistic effect between CoSi and Pd. The novel multi-effects of Pd on CoSi make Pd/CoSi–G a highly active, durable and low-cost fuel cell electrocatalyst candidate.